PRESENTASI MATEMATIKA SISWA PADA PENERAPAN PENDEKATAN MATEMATIKA REALISTIK DALAM PELAKSANAAN LESSON STUDY DI SEKOLAH MENENGAH PERTAMA (Proceeding 7th International Seminar on Regional Education, 2015)
AbstractThis study is conducted by applying mathematical representative at junior high school students in Pekanbaru, Riau. This study is conducted while teaching Lesson Study by using mathematical realistic approach and took place in Junior High School 13 in Pekanbaru at even semester, lesson year 2015/2016 with total 38 students of 1st year class. The implementation of lesson study consists of 4 cycles which is in each cycle made of planning, doing, and monitoring. The mathematical representative applied in this study are including pictorial representation and mathematics symbol representation. The result of this study shows that there is an increase in studentâs mathematical representation of every cycle and the most of students prefer mathematics symbol (100%) to diagrammatically and graphically representation (29,41%) and explanned word with verbal (44.121%) . This study also produces an improvement of student worksheet and gets an increase in student activity.Keyword :Representation mathematics,Lesson Study and Realistics Mathematics approach